Assessment of Yield Loss in Green Gram (Vigna radiate (L) R. Wilczek) Cultivation and Estimation of Weed-Free Period for Eco-Friendly Weed Management - Kumara, P.; Deepani, L.P.P. (1st International Electronic Conference Agronomy Volume: 1, 2021)
Fabaceae member green gram (Vigna radiata (L.) R. Wilczek) is one of the most economically important grain legumes of traditional farming systems of Sri Lanka because of its cheap sources of protein, animal feed, and in sustaining soil fertility by fixing atmospheric nitrogen. Weeds are one of the major problems in mung bean cultivation, reduce the yield through competition, interference with harvest and harbouring pest and diseases. Controlling of weeds by applying herbicides definitely would cause unexpected damage to human health and abundant biodiversity of Sri Lanka. Therefore, an investigation was planned to evaluate the yield loss due to weeds and to determine the optimum weed free period to minimize the yield losses. Three categories of trial plots were established. Plot one was maintained to determine the effect of different weed categories on the yield of the mung bean, in second category weeds were continuously hand weeded and kept weed free, and in third, weeds were allowed to compete with mung bean until 2, 3, 4, 5, 6 weeks after cultivation. All the treatments were conducted in Randomized Complete Block Design with three replicates. The data collected on types of weed, category of weeds, number of pods, pod weight at 3–6 weeks after planting (WAP) were analysed using SAS 9.4 statistical package and DMRT was performed to know the best treatment combination at p value of 0.05. The results showed that average yield loss due to total weed populations were 54.77%. Yield loss due to grasses alone were 46.56% and significant, in comparison to broad leaves (16.49%) and sedges (18.01%) at p < 0.05, respectively. The data of plant stand count at 3–4 WAP were not showed significant difference among treatments. But biomass weight of 50 plants, number of pods in 50 plants and grain weight of 10 plants were found to be significant after 3–4 WAP in weed free conditions at p < 0.05%. In the weed free in the whole season obtained higher plot yield was 1241.6g and this was significant when weed was competing after 4 weeks of planting (1083.3 g). According to the results of the present study, it can be concluded that the critical weed free period until 3 to 4 WAP. Maintaining of weed free period of 3–4 weeks is recommended to minimize the yield loss in the green gram.
Keywords: critical weed free period; mung bean; weed; weed competition; yield loss due to weeds